Pro SQL Server 2005 Assemblies - Dewson, Robin; Skinner, Julian (Apress : Imprint: Apress, 2006)
Pro SQL Server 2005 Assemblies provides a detailed and example-driven tutorial on how to build and use .NET assemblies. The authors focus on building assemblies in C#, but also provide the equivalent VB .NET code in the supplied code download. Assemblies are not a complete replacement for T-SQL stored procedures and triggers; rather, they're enhancements, to be used at the right place and right time. This book examines the ins and outs of assemblies when they should and should not be used, what you can do with them, and how you can get the most out of them.